PROVENANCE OF NORTH GONDWANA CAMBRIAN-ORDOVICIAN SANDSTONE: U-PB SHRIMP DATING OF DETRITAL ZIRCONS FROM ISRAEL AND JORDAN - Kolodner K.; Avigad D.; McWILLIAMS M.; Wooden J.L.; Weissbrod T.; Feinstein S. (My University, 2006)
A vast sequence of quartz-rich sandstone was deposited over North Africa and Arabia during Early Palaeozoic times, in the aftermath of Neoproterozoic Pan-African orogeny and the amalgamation of Gondwana. This rock sequence forms a relatively thin sheet (1-3 km thick) that was transported over a very gentle slope and deposited over a huge area. The sense of transport indicates unroofing of Gondwana terranes but the exact provenance of the siliciclastic deposit remains unclear. Detrital zircons from Cambrian arkoses that immediately overlie the Neoproterozoic Arabian-Nubian Shield in Israel and Jordan yielded Neoproterozoic U-Pb ages (900-530 Ma), suggesting derivation from a proximal source such as the Arabian-Nubian Shield. A minor fraction of earliest Neoproterozoic and older age zircons was also detected. Upward in the section, the proportion of old zircons increases and reaches a maximum (40%) in the Ordovician strata of Jordan. The major earliest Neoproterozoic and older age groups detected are 0.95-1.1, 1.8-1.9 and 2.65-2.7 Ga, among which the 0.95-1.1 Ga group is ubiquitous and makes up as much as 27% in the Ordovician of Jordan, indicating it is a prominent component of the detrital zircon age spectra of northeast Gondwana. The pattern of zircon ages obtained in the present work reflects progressive blanketing of the northern Arabian-Nubian Shield by Cambrian-Ordovician sediments and an increasing contribution from a more distal source, possibly south of the Arabian-Nubian Shield. The significant changes in the zircon age signal reflect many hundreds of kilometres of southward migration of the provenance.
Keywords: ZIRCON; CAMBRIAN-ORDOVICIAN; ARABIAN-NUBIAN SHIELD; PROVENANCE; Paleozoic::Ordovician; Палеозой::Кембрийская; Докембрий::Протерозой::Неопротерозойская; Палеозой::Ордовикская; Paleozoic::Cambrian; Precambrian::Proterozoic::Neoproterozoic